Throughput Improvement of High Density Wireless Personal Area Networks - Vatti, Rambabu A.; Gaikwad, Arun N. (2014 International Conference on Computational Intelligence and Communication Networks, 2014)
Throughput is the key parameter used to estimate the quality of service of the Wireless Personal Area Network (WPAN). Energy efficiency and security are the important parameters to be addressed after network achieves required level of quality of service. Many research papers have been published on the subject of energy efficiency, but the throughput of the Wireless Personal Area Networks has not been extensively investigated. In this paper, we focus on throughput improvement of Low Rate WPANs. The IEEE 802.15.4 Low Rate WPAN standard is designed for short range wireless communication based on low power consumption and low cost. In these networks, the communication capacity is limited by the low hardware specifications of the sensor nodes such as limited memory capacity and low processing speed. The authors attempt to address the low memory capacity problem in this paper. Due the exponential growth in the Low Rate WPAN applications in the consumer field, high density networks are most commonly in place. In high density wireless networks, congestion occurs at Cluster Heads (CH) and at the coordinator. As a result of this, some of the packets are dropped and the network throughput is degraded. The authors propose Rate Adjustment Algorithm (RAA) to avoid the congestion at the coordinator. The RAA monitors the buffer occupancy level at the coordinator and informs the current status of the buffer occupancy level to the transmitting nodes and cluster heads using a modified beacon frame. Based on the current buffer occupancy level, the transmitting nodes will either decrease their data transmission rate to reduce the congestion at the coordinator, or increase the data transmission rate to avoid the underutilization of the network. In both the cases, the throughput will be improved. The simulation results show a 31% improvement in throughput with the proposed algorithm RAA.